The combination of blueberry juice and probiotics reduces apoptosis of alcoholic fatty liver of mice by affecting SIRT1 pathway - Zhu J; Ren T; Zhou M; Cheng M (Dove Medical Press, 2016)
Juanjuan Zhu,1,2,* Tingting Ren,3,* Mingyu Zhou,2 Mingliang Cheng2 1First Hospital Affiliated to Suzhou University, Suzhou, 2Department of Infectious Diseases, 3Biochemistry Department, Affiliated Hospital of Guiyang Medical College, Guiyang, People’s Republic of China *These authors contributed equally to this work Purpose: To explore the effects of the combination of blueberry juice and probiotics on the apoptosis of alcoholic fatty liver disease (AFLD).Methods: Healthy C57BL/6J mice were used in the control group (CG). AFLD mice models were established with Lieber–DeCarli ethanol diet and evenly assigned to six groups with different treatments: MG (model), SI (SIRT1 [sirtuin type 1] small interfering RNA [siRNA]), BJ (blueberry juice), BJSI (blueberry juice and SIRT1 siRNA), BJP (blueberry juice and probiotics), and BJPSI (blueberry juice, probiotics, and SIRT1 siRNA). Hepatic tissue was observed using hematoxylin and eosin (HE) and Oil Red O (ORO) staining. Biochemical indexes of the blood serum were analyzed. The levels of SIRT1, caspase-3, forkhead box protein O1 (FOXO1), FasL (tumor necrosis factor ligand superfamily member 6), BAX, and Bcl-2 were measured by reverse transcription-polymerase chain reaction and Western blotting.Results: HE and ORO staining showed that the hepatocytes were heavily destroyed with large lipid droplets in MG and SI groups, while the severity was reduced in the CG, BJ, and BJP groups (P<0.05). The levels of superoxide dismutase (SOD), reduced glutathione (GSH), and high-density lipoprotein-cholesterol (HDL-C) were increased in BJ and BJP groups when compared with the model group (P<0.05). In contrast, the levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT), total triglycerides (TGs), total cholesterol, low-density lipoprotein-cholesterol (LDL-C), and malondialdehyde (MDA) were lower in BJ and BJP groups than in the model group (P<0.05). The level of SIRT1 was increased, while the levels of FOXO1, phosphorylated FOXO1, acetylated FOXO1, FasL, caspase-3, BAX, and Bcl-2 were decreased in CG, BJ, and BJP groups (P<0.05). Meanwhile, SIRT1 silence resulted in increase of the levels of FOXO1, phosphorylated FOXO1, acetylated FOXO1, FasL, caspase-3, BAX, and Bcl-2.Conclusion: The combination of blueberry juice and probiotics reduces apoptosis in AFLD by suppressing FOXO1, phosphorylated FOXO1, acetylated FOXO1, FasL, caspase-3, BAX, and Bcl-2 via the upregulation of SIRT1. Keywords: alcoholic fatty liver, blueberry, caspase-3, forkhead box protein O1, probiotics, sirtuin type 1, tumor necrosis factor ligand superfamily member 6